Around quitting time : work and middle-class fantasy in American fiction - Seguin, Robert, 1963- (New Americanists., 2001)
Posits social class as the American political unconscious, showing (in an analysis of 19th and 20th century novels) how class exerts pressure on the American cultural imagination, and claiming that what is desired is ultimately the liberation from work.